Integrated strategy for berth allocation and crane assignment on a continuous berth using Monte Carlo simulation. (January 2015) - Ji, Mingjun; Zhu, Huiling; Wang, Qingbin; Zhao, Rui; Yang, Yongzhi
The designation of berths, the service strategy for vessels and the assignment of cranes are important for improving the operational efficiency of container terminals. The berth may be discrete or continuous, we focus on the continuous situation. In this paper we first establish an evaluation index system for describing continuous berth allocation, service strategy for vessels and assignment of cranes. We then design Monte Carlo method to simulate different scenarios of operation and calculate various performance indices. The data is analyzed by variance and sensitivity analysis. We finally use the index values to design reasonable operation schedules for integrating berth allocation and crane assignment.